The Strengthening Customary Land Rights: Promoting Agrarian Law Reform in Indonesia - Widiyoko, Setiawan; Wiranto, Agus Prasetia (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
Ulayat land is land that is controlled jointly by members of a customary law community, where the management arrangements are carried out by the traditional leader (Head of Adat) and its use is intended for both members of the customary law community concerned and outsiders. Indigenous communities tend to live scattered across Indonesia's vast forest areas. With the issuance of the Basic Agrarian Law (UUPA) and development programs, they are threatened with eviction from the forest land they now occupy. This is based on confusion regarding the legal position and rights of indigenous peoples to customary land and other agrarian resources. The existence of indigenous peoples and their rights to land is one of the considerations in renewing the law on agrarian affairs, especially in reforming agrarian law. This research was carried out using a normative juridical method. Data was obtained by collecting from several sources such as books, journal articles and regulations. In conclusion, the recognition of customary land rights has been regulated in the Basic Agrarian Law Articles 3 and 5 of 1960 and is in the process of being implemented. In the field there are many agrarian disputes that are detrimental to customary land and there is no clarity on the process of protecting customary land.